Theoretical, Numerical and Experimental Researches on Time-Varying Dynamics of Telescopic Wing. (31st March 2022) - Zhang, W.; Gao, Y.H.; Lu, S.F.
Highlights: Stability and vibration of telescopic wing are studied. Telescopic wing is simplified to a telescopic plate subjected to first-order aerodynamic force and in-plane excitation. Time-varying dynamic properties of telescopic plate are investigated by using analytical, numerical and experimental methods. Approximate analytical results demonstrate a good agreement. Experimental results are consistent with the theoretical results. Abstract: The stability and vibration of the telescopic wing are studied by the theoretical, numerical and experimental methods when the wing is in the deployment and retraction. The telescopic wing is simplified to a telescopic cantilevered laminated composite rectangular plate subjected to the first-order aerodynamic force and in-plane excitation. The time-varying dynamic characteristics of the telescopic cantilevered laminated composite rectangular plate are investigated by using the analytical, numerical and experimental methods. The approximate analytical solution of the nonlinear time-varying system is obtained by using the improved averaging method. Compared with numerical simulations, the approximate analytical results demonstrate a good agreement. The stability of the telescopic cantilever plate during the deploying process is studied by using the eigenvalue method, which demonstrates the effect of the velocity, acceleration and thickness on the stability of the deployment. The experimental results are consistent with the theoretical results and provide the theoretical basis and technical support for the axial moving wing.